Socio-political drivers and consequences of landslide and flood risk zonation: A case study of Limbe city, Cameroon. (June 2019) - Maes, Jan; Molombe, Jeff Mbella; Mertens, Kewan; Parra, Constanza; Poesen, Jean; Che, Vivian Bih; Kervyn, Matthieu
Disaster risk zonation is often proposed as a long-term disaster risk reduction strategy by international treaties and academic research. This strategy has been implemented in the city of Limbe, which is known to be a disaster-prone one. Citizens are forced to settle in unsafe terrains, ranging from wetlands to unstable hillslopes due to the city's geographical location and economic attraction. Following the fatal landslides and floods in 2001, a local crisis committee identified affected areas and declared them 'risk zones' to prevent further exposure. Empirically, this study narrates the production and implementation of risk zonation policy in the city of Limbe. Theoretically, it uses an urban political ecology perspective, which incorporates science and technology studies, post-political theory and disaster research to interpret the drivers and implications of the mismatch between research, policy and action. In this case study, we investigate the implications for disaster risk reduction by describing three underlying socio-political drivers of the risk zonation policy: (i) authoritarian science regime, (ii) post-political discourse, and (iii) blame diversion. We argue that authorities from national to local level use a post-political discourse to promote and implement disaster risk reduction in the city of Limbe through the development and the application of risk zonation policy. As a consequence, risk zonation leads to poor enforcement of the law and corruption, ultimately leading to risk accumulation in this case. This analysis allows us to draw broader conclusions on drivers and implications of the implementation of disaster risk zonation policy in urban areas that are primarily governed hierarchically and prone to corruption.